Implementation of Audio-Computer Assisted Self-Interview (ACASI) among adolescent girls in humanitarian settings: feasibility, acceptability, and lessons learned. Issue 1 (December 2016) - Falb, Kathryn; Tanner, Sophie; Asghar, Khudejha; Souidi, Samir; Mierzwa, Stan; Assazenew, Asham; Bakomere, Theresita; Mallinga, Pamela; Robinette, Katie; Tibebu, Woinishet; Stark, Lindsay
Abstract Background Audio-Computer Assisted Self- Interview (ACASI) is a method of data collection in which participants listen to pre-recorded questions through headphones and respond to questions by selecting their answers on a touch screen or keypad, and is seen as advantageous for gathering data on sensitive topics such as experiences of violence. This paper seeks to explore the feasibility and acceptability of using ACASI with adolescent girls and to document the implementation of such an approach in two humanitarian settings: conflict-affected communities in eastern Democratic Republic of Congo (DRC) and refugee camps along the Sudan-Ethiopia border. Methods This paper evaluates the feasibility and acceptability of implementing ACASI, based on the experiences of using this tool in baseline data collections for COMPASS (Creating Opportunities through Mentorship, Parental involvement, and Safe Spaces) impact evaluations in DRC (N = 868) and Ethiopia (N = 919) among adolescent girls. Descriptive statistics and logistic regression models were generated to examine associations between understanding of the survey and selected demographics in both countries. Results Overall, nearly 90% of girls in the DRC felt that the questions were easy to understand as compared to approximately 75% in Ethiopia. Level of education, but not age, was associated with understanding of the survey in both countries. Conclusions Financial and time investment to ready ACASI was substantial in order to properly contextualize the approach to these specific humanitarian settings, including piloting of images, language assessments, and checking both written translations and corresponding verbal recordings. Despite challenges, we conclude that ACASI proved feasible and acceptable to participants and to data collection teams in two diverse humanitarian settings.